Eutopie glocali per il Sud Italia. Sull’ermeneutica del soggetto di Lecce, Matera e Venezia, candidate italiane a Capitale europea della Cultura 2019 - Sambre, Paul; Van den Bogaert, Annelies (Incontri. Rivista europea di studi italiani, 2016)
Global eutopias for Southern Italy: about the hermeneutics of the subject of Lecce, Matera and Venice, Italian candidate cities for European Capital of Culture 2019This article proposes a critical discourse analysis (CDA) of a debate between the Italian applicant cities seeking the title of European Capital of Culture 2019. The discourse concerning the cultural future of these cities highlights a process of change, involving different configurations of institutional stakeholders and/or local grassroots communities, which, top-down and/or bottom-up, reinvent the historical past of the city in order to comply with institutional EU requirements regarding the impact of regions on common European cultural heritage. The approaches adopted by Venice, Matera and Lecce are quite different in this respect: whereas Venice insists on its position within a cultural, economic and multilingual transnational macro-region, Matera reinvents itself as a new regional meeting ground between a local and global European culture, as a Southern (Italian) city that can offer universal values to Europe as a whole, such as the notion of shame in times of crisis. At a theoretical level, discussion of the candidature of these potential future capitals of culture offers a corpus in which the discourse of social change, central to CDA, can be observed. Given the dynamic interplay between political requirements and regional activism (less present in Lecce’s arguments) in the ECoC proposals, this research calls for an epistemological updating of CDA’s archaeological and static view on the Foucauldian relation between subjects and power in favor of Foucault’s late hermeneutic of the self-constituting subject.